"All these little pushes and nudges": uncovering ordinary beliefs about God's work in the pre-christian life. Issue 2 (15th March 2019) - Milton, G.
ABSTRACT: In the Classical Pentecostal movement, theologies of religion have historically been shaped by an adopted exclusivist model, whereby there can be no salvation apart from Christ. Since the end of the last century, Pentecostal scholars have been making headway in challenging this stereotype and exploring other possible avenues for a uniquely Pentecostal theology of religions. By exploring the ordinary theology of interview participants, this article contributes to the discussion in two main ways: (1) by mapping some of the ways that ordinary believers consider God to have been at work in their life before becoming a Christian, and (2) by critically analysing assumptions that emerge from this ordinary theology and the implication of these for an ever-developing Pentecostal theology of religions.